A cross-sectional study to evaluate uploader-based quality and reliability of content on YouTube about endometriosis - Clarke, Shereece; Ghotra, Monica; Kuruvila, Mahima; Venkatraman, Aarushi; Upadrasta, Vasishtha A.; Melnyk, Khrystyna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Endometriosis is characterized by the development and presence of endometrial glands and stroma outside of the uterine cavity. Reflux of endometrial tissue fragments, cells, and protein-rich fluid into the pelvis during menstruation is considered the most important mechanism for the development of endometriosis, which is termed reflux menstruation. This study aims to assess quality and reliability of information on YouTube related to endometriosis. Methods: A cross-sectional observational study of YouTube videos was conducted in April 2023. Videos related to endometriosis were searched by six authors, easy using one search term. Relevant videos in English or Hindi language of duration 1-20 minutes were included in the study. These were evaluated for type of uploader, popularity, type of content and lastly quality and reliability using global quality score (GQS) and DISCERN scores respectively. Results: The 67 relevant videos conveying Endometriosis related information had 21,620,808 views, 120,830 likes and 11,655 comments. Around 31 (46.3%) of videos uploaded were by doctors and health care organizations, outnumbering those uploaded by news channels 14 (20.9%), patients 5 (7.5%), and others 17 (25.4%). 59 (88.06%) of these videos described symptoms of endometriosis, and 67.1% presented the cause or etiology. A total of 47 (70.1%) of videos discussed information regarding treatment options. Conclusions: YouTube videos have a wide reach among audience. In this study it was found that there was no significant difference in the quality, reliability or video power index (VPI) of videos uploaded by different types of uploaders. It is important to ensure that content with high quality and reliability is available from qualified medical professionals and organizations; for viewers to understand their disease and take treatment decisions.